A People's History of the Russian Revolution - Faulkner, Neil (Left Book Club, 2017)
The Russian Revolution was an explosion of mass democracy from below. It transformed the people who took part and inspired tens of millions across the world. Its global impact shook the capitalist system to its foundations and came close to bringing it down. But in the end, the revolutionary movement was destroyed by the most murderous counter-revolutionary terror in history. And because the real history of the revolution is so subversive of class rule everywhere - East, West, and South - it has been buried under a mountain of lies, distortions, and denials. This book sets out to nail every bogus argument about the Russian Revolution - from Tories, Stalinists, and sectarians - and to present the living reality of a mass movement of millions, organised in participatory assemblies, mobilised for militant action.